God's Perfect Will: Remarks on Johnston and O'Connor - Pearce, Kenneth (Oxford University Press, 2022)
How can God's creative decision be free? Why would God create anything at all? Why would God create a world like this one, with all of its evils? These puzzles lie at the heart of classical theism. Mark Johnston has argued that all three can be solved by adopting the Neoplatonic thesis that God's willing is an affirmation of God's own goodness. Timothy O'Connor argues (among other things) that Johnston overestimates the extent of divine freedom secured by this strategy. I argue that O'Connor does not go far enough: although the Neoplatonic framework provides a promising answer to the question of why God would create at all, it makes no progress on the problem of divine freedom or the problem of evil. Indeed, the Neoplatonic framework itself was partly responsible for driving ibn Sina and Leibniz to the implausible conclusion that, necessarily, God creates the best of all possible worlds.
Oxford Studies in Philosophy of Religion Volume 10
PUBLISHED
Invited symposium contribution
Oxford
Keywords: Philosophy of religion